Transnationality And Nationalism: Shared And Contested Memories Of Wu Lien-teh Across East And Southeast Asia In Post-sars Era - Por , Heong Hong (Penerbit Universiti Sains Malaysia (USM Press), 2016)
Maurice Halbwachs proposed that the reading of the pasts is shaped by interests and needs of the present. The surging interest in Wu Lien-Teh— Penang-born, Cambridge-trained plague fighter in China—across East and Southeast Asia in post-SARS era appears to affirm Halbwachs' view. Utilising Halbwachs' presentist and constructionist approach, this article reads post-SARS memories of Wu Lien-Teh as a contested terrain where various historical actors, under a mix of fortuitous as well as intentional circumstances, come to construct what they presently perceive as relevant and important. Memories of the past is thus a site that tells about the present. Drawing on a variety of publications and online sources, this article makes post-SARS accounts of Wu in the region a case for the study of how the pasts are reconstructed to communicate the present. Given that the commemoration of Wu spans across various countries, the case also allows investigation of memory variation across the region. The findings show that the reconstruction of Wu's pasts in the region has been shaped by varying subjective concerns of different historical actors, politics and social conditions in the region, and the transnationality, locality and materiality of Wu's legacies.